1991
DOI: 10.1073/pnas.88.4.1227
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 2 induces tyrosine phosphorylation and activation of p72-74 Raf-1 kinase in a T-cell line.

Abstract: Interleukin 2 (IL-2) is a lymphokine, produced by T cells upon antigenic or mitogenic stimulation, that is a critical regulator of T-cell proliferation. Although the binding of IL-2 to its receptor has been well characterized, the molecular mechanisms by which IL-2 transmits its signal from the membrane to the interior of the cell are poorly understood. Like most other growth factors, IL-2 causes rapid phosphorylation of proteins within its target cells. Unlike many other growth factors, however, the known sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
1
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(74 citation statements)
references
References 36 publications
3
69
1
1
Order By: Relevance
“…particularly in cells of hematopoietic origin (Carroll et al, 1991;Turner et al, 1991), in cells transformed by oncogenic Ras (Jelinek et al, 1996) and in cells exposed to ionizing radiation (Kasid et al, 1996). Furthermore, experiments in both mammalian and Sf9 cells have implicated two adjacent tyrosine residues in the catalytic domain of Raf-1 (Y340 and Y341) as being important for the regulation of Raf-1 kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…particularly in cells of hematopoietic origin (Carroll et al, 1991;Turner et al, 1991), in cells transformed by oncogenic Ras (Jelinek et al, 1996) and in cells exposed to ionizing radiation (Kasid et al, 1996). Furthermore, experiments in both mammalian and Sf9 cells have implicated two adjacent tyrosine residues in the catalytic domain of Raf-1 (Y340 and Y341) as being important for the regulation of Raf-1 kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…As is typical of type I cytokine receptors, neither IL-2Rb nor g c contains protein kinase activity in its cytoplasmic domain (Hatakeyama et al, 1989;Takeshita et al, 1992). However, within minutes following the interaction of IL-2 with the high-or intermediate-a nity IL-2 receptors, a number of cellular proteins, including IL2Rb and g c , are phosphorylated on tyrosine residues (Farrar and Ferris, 1989;Turner et al, 1991), at least in part by the receptor-associated protein tyrosine kinases, Jak1 and Jak3 (Friedmann et al, 1996;Johnston et al, 1994;Witthuhn et al, 1994). It has been demonstrated that in the absence of IL-2, Jak1 is associated with IL-2Rb Russell et al, 1994;Witthuhn et al, 1994) and Jak3 is with g c Russell et al, 1994;Figure 2).…”
Section: How Does Il-2 Transduce Its Signals?mentioning
confidence: 99%
“…An important pathway activated following stimulation by IL-2 is the Ras-Raf-MAP kinase pathway (Graves et al, 1992;Turner et al, 1991Turner et al, , 1993Zmuidzinas et al, 1991; Figure 2). The adaptor protein Shc associates with Tyr-338 of IL-2Rb via its PTB domain and it is tyrosine phosphorylated by Jak1 (Friedmann et al, 1996;Ravichandran et al, 1996).…”
Section: How Does Il-2 Transduce Its Signals?mentioning
confidence: 99%
“…In addition to activating a variety of tyrosine kinases (2), IL-2 also activates other signaling molecules, including serine kinases (50) and Ras (51). The COS-7 reconstitution system reported herein may be valuable in screening transfected gene products to help identify other signaling molecules required for mediating IL-2-dependent, Stat5-mediated transcription and in clarifying whether Stat5A homodimers, Stat5B homodimers, and Stat5A-Stat5B heterodimers regulate the same or different genes.…”
Section: Isolation Of Two Closely Related Human Stat5 Cdnas Whosementioning
confidence: 99%